Application of POE (Predict, Observe, Explain) Learning Model to Improve Understanding of Concepts - Dewi, Imega Syahlita; Rahmawati, Maylinda Dwi (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
This research aims to determine the POE (Predict, Observe, Explain) learning model in improving students' understanding of concepts in the Chemistry subject at SMA Negeri 1 Gondang. This research method uses a class action research model. The research subjects were 35 students in class X-4. This research has a good impact on students' understanding of concepts, this can be conveyed through the results of cycle I and cycle II research. Cycle I completed 25 students with a completion percentage of 71.4%, while cycle II completed 28 students with a completion percentage of 82.9%. So in cycle I and cycle II there was an increase in students' understanding of concepts in the Chemistry subject. Keywords: POE, Concept Understanding, Chemistry